ANALISIS KELAYAKAN USAHA PETERNAKAN AYAM PETELUR CLOSED HOUSE - Lambok Rommy Sulaeman; Ade Oki Pebiansyah; Deni Utama; Berliana, Berliana (Media Bina Ilmiah, 2024)
This study aims to analyse the business feasibility of closed house layer farmers. The business feasibility criteria used are: Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Periods. The results of the analysis can be stated that the business of laying hens is feasible or recommended "GO" to be cultivated/developed on a larger scale. This refers to the results of the financial analysis obtained in this study, which has a level of ability to return investment costs (IRR) above the discount factor value, meaning that the closed house layer farming business that is cultivated by farmers is able to provide a large level of profit so that the time to return investment costs can be done in a relatively fast time, so that the remaining revenue from the laying hen farming business activities is entirely a profit for farmers.